Immunomodulatory glc/man-directed Dolichos lablab lectin (DLL) evokes anti-tumour response in vivo by counteracting angiogenic gene expressions. (5th April 2017) - Vigneshwaran, V; Thirusangu, P; Vijay Avin, B R; Krishna, V; Pramod, S N; Prabhakar, B T
Summary: Neovascularization and jeopardized immunity has been critically emphasized for the establishment of malignant progression. Lectins are the diverse class of carbohydrate interacting proteins, having great potential as immunopotentiating and anti-cancer agents. The present investigation sought to demonstrate the anti-proliferative activity of Dolichos lablab lectin (DLL) encompassing immunomodulatory attributes. DLL specific to glucose and mannose carbohydrate moieties has been purified to homogeneity from the common dietary legume D. lablab . Results elucidated that DLL agglutinated blood cells non-specifically and displayed striking mitogenicity to human and murine lymphocytes in vitro with interleukin (IL)-2 production. The DLL-conditioned medium exerted cytotoxicity towards malignant cells and neoangiogenesis in vitro . Similarly, in-vivo anti-tumour investigation of DLL elucidated the regressed proliferation of ascitic and solid tumour cells, which was paralleled with blockade of tumour neovasculature. DLL-treated mice showed an up-regulated immunoregulatory cytokine IL-2 in contrast to severely declined levels in control mice. Mechanistic validation revealed that DLL has abrogated the microvessel formation by weakening the proangiogenic signals, specifically nuclear factor kappa B (NF-κB), hypoxia inducible factor 1α (HIF-1 α), matrix metalloproteinase (MMP)-2 and 9 and vascular endothelial growth factor (VEGF) in malignant cells leading to tumour regression. In summary, it is evident that the dietary lectin DLL potentially dampens the malignant establishment by mitigating neoangiogenesis and immune shutdown. For the first time, to our knowledge, this study illustrates the critical role of DLL as an immunostimulatory and anti-angiogenic molecule in cancer therapeutics. Graphical Abstract: